2022
DOI: 10.1021/acsanm.2c04267
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneously Stretchable and Compressible Flexible Strain Sensors Based on Carbon Nanotube Composites for Motion Monitoring and Human–Computer Interactions

Abstract: Simultaneously stretchable and compressible flexible strain sensors are highly desired in many advanced applications including the wearable field. However, the fabrication of such dual-function sensors with a wide sensing range is still challenging. In this work, a simultaneously stretchable and compressible foam strain sensor was fabricated by skillfully introducing oriented pores into the highly stretchable elastic composite based on carbon nanotubes and poly(styrene-b-ethylene–butylene-b-styrene) (SEBS) by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 56 publications
(90 reference statements)
0
8
0
Order By: Relevance
“…Researchers have attempted to transform sign language into recognizable signals to facilitate online communication for deaf people. Strain sensors are usually used to capture the response signals generated by the bending of different fingers to represent the letters in sign language. However, it is not possible to recognize all the sign language gestures by the response signals of finger bending alone; for example, the sign language gestures representing the letters C, E, O, and S all require the bending of five fingers, which results in the same response signals for these gestures. Analyzing the sign language gestures, we found that the sign language gestures representing the 26 letters of the alphabet can be fully recognized by the difference in the response signals captured by the sensors for finger bending and fingertip pressing.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Researchers have attempted to transform sign language into recognizable signals to facilitate online communication for deaf people. Strain sensors are usually used to capture the response signals generated by the bending of different fingers to represent the letters in sign language. However, it is not possible to recognize all the sign language gestures by the response signals of finger bending alone; for example, the sign language gestures representing the letters C, E, O, and S all require the bending of five fingers, which results in the same response signals for these gestures. Analyzing the sign language gestures, we found that the sign language gestures representing the 26 letters of the alphabet can be fully recognized by the difference in the response signals captured by the sensors for finger bending and fingertip pressing.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Introducing microstructures such as pyramids, micropillars, hemispheres, or biomimetic microstructures , into flexible substrates can improve the sensitivity and linear response range of the sensors. Functional materials with excellent performance include silver nanowires (AgNWs), graphene, graphene oxide (GO), , carbon nanotubes (CNTs), and carbon black (CB) , and have been widely explored as conductive fillers or sensing units for sensors to construct conductive networks for high-performance sensing. The porous structure increases the compression range of the elastic body due to the existence of a large number of micropores, which makes the flexible pressure sensor with porous structure easy to deform and extremely sensitive even under small pressure. , Many methods for the introduction of micropores have been reported, including a salt or sugar template method, , a porous sponge template, and three-dimensional (3D) printing …”
Section: Introductionmentioning
confidence: 99%
“…By improving the electrical properties of the hydrogel, it makes the hydrogel applicable for direct use as a sensing material for strain sensors and wearable electronic devices. Heretofore, multiple conductive materials have been included into hydrogels to produce conductive hydrogels, such as carbon nanomaterials, inorganic nanoparticles/nanowires, and conductive polymers. …”
Section: Introductionmentioning
confidence: 99%